ISIS Use of Twitter to Appeal to Saudis: Experts’ Views on Saudi Counter-Measures - Hamad Alqurainy, Sara; Hamedi M., Adnan (Opción, 2019)
The so-called Islamic State in Iraq and Syria (ISIS) has a thorn in neck for many countries around the world. ISIS has made no secret about its desire to conquer the Kingdom of Saudi Arabia via every means possible. One of the medium through which ISIS targets Saudi Arabia is the use of Twitter to exploit Saudis obsessive Twitter use. The aim of this paper to seek experts’ opinions on ISIS targeting Sau- dis via the Twitter and measures taken by the Saudi authorities. To achieve the aforementioned objective, ten experts from the academia, security/cyber security and media and communication background were interviewed. The data was ana- lysed through reflexive thematic analysis with the aid of Nvivo 12 Pro software. Finding of the interviews leads to the extraction of a number of themes. This study is expected to offer insight into the counter-measures taken in fighting ISIS Twitter and, to some extent, social media onslaught, particularly against the Kingdom of Saudi Arabia.